Superconductive Supercooling and Superheating of Small Cadmium Spheres: Size Effects - de la Cruz, F.; Maloney, M.D.; Cardona, M. (American Physical Society, 1971)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Brown University. Department of Physics; Estados Unidos